2021
DOI: 10.3390/biology10100978
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Urocortin 3 mRNA in the Central Nervous System of the Sea Lamprey Petromyzon marinus

Abstract: In this study, we analyzed the organization of urocortin 3 (Ucn3)-expressing neuronal populations in the brain of the adult sea lamprey by means of in situ hybridization. We also studied the brain of larval sea lampreys to establish whether this prosocial neuropeptide is expressed differentially in two widely different phases of the sea lamprey life cycle. In adult sea lampreys, Ucn3 transcript expression was observed in neurons of the striatum, prethalamus, nucleus of the medial longitudinal fascicle, torus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Figure 9 shows photomicrographs of sections of prolarval heads processed for PmCRH ISH, PmCRHBP ISH or for PmCRH immunohistochemistry. The terminology employed in this study for the various regions, nuclei, tracts, and identified neurons followed those used in other studies of lamprey neuropeptides of our group (see Sobrido-Cameán et al, 2019, 2020b, 2021a). Since the same positive populations found by PmCRH ISH were also observed by PmCRH immunofluorescence, we assumed that the antibody recognized only this PmCRH peptide.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 9 shows photomicrographs of sections of prolarval heads processed for PmCRH ISH, PmCRHBP ISH or for PmCRH immunohistochemistry. The terminology employed in this study for the various regions, nuclei, tracts, and identified neurons followed those used in other studies of lamprey neuropeptides of our group (see Sobrido-Cameán et al, 2019, 2020b, 2021a). Since the same positive populations found by PmCRH ISH were also observed by PmCRH immunofluorescence, we assumed that the antibody recognized only this PmCRH peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is probable that PmCRHBP binds to several members of the CRH family of lampreys. The brain distribution of the mRNA of another member of the CRH gene family (Ucn3) has been recently studied by our group (Sobrido-Cameán et al, 2021a). Comparison of Ucn3 distribution results in sea lamprey with present PmCRH distribution reveals important differences between the distributions of these substances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations